Ground Reaction Forces of the Lead and Trail Limbs when Stepping Over an Obstacle - Bovonsunthonchai, Sunee (Med Sci Monit, 2015)
BACKGROUND: Precise force generation and absorption during stepping over different obstacles need to be quantified for task accomplishment. This study aimed to quantify how the lead limb (LL) and trail limb (TL) generate and absorb forces while stepping over obstacle of various heights. MATERIAL/METHODS: Thirteen healthy young women participated in the study. Force data were collected from 2 force plates when participants stepped over obstacles. Two limbs (right LL and left TL) and 4 conditions of stepping (no obstacle, stepping over 5 cm, 20 cm, and 30 cm obstacle heights) were tested for main effect and interaction effect by 2-way ANOVA. Paired t-test and 1-way repeated-measure ANOVA were used to compare differences of variables between limbs and among stepping conditions, respectively. The main effects on the limb were found in first peak vertical force, minimum vertical force, propulsive peak force, and propulsive impulse. RESULTS: Significant main effects of condition were found in time to minimum force, time to the second peak force, time to propulsive peak force, first peak vertical force, braking peak force, propulsive peak force, vertical impulse, braking impulse, and propulsive impulse. Interaction effects of limb and condition were found in first peak vertical force, propulsive peak force, braking impulse, and propulsive impulse. CONCLUSIONS: Adaptations of force generation in the LL and TL were found to involve adaptability to altered external environment during stepping in healthy young adults.